The impact of information technology on information professionals in academic libraries / Norshidah Mohd Idris - Mohd Idris, Norshidah (2000)
Information technology has created an interactive and expansive quality to information not experienced previously thus contributing to information becoming a primary commodity in the global market today including the academic world. Academic librarians in academic libraries are challenged to rethink the way they define the vocation of librarianship due to the impact of information technology to their profession. Thus they are exploring new opportunities and implement change in establishing new roles, responsibilities, skills and abilities in providing quality services to the community they serve. Their evolving roles as they move into the 21st century will be determined by the actions, decisions taken and examples set today. It is vital for librarians to "embrace" change to ensure the continual growth of their profession in the university.